Psychological morbidity of celiac disease: a review of the literature - Zingone, Fabiana; Swift, Gillian L; Card, Timothy R.; Sanders, David S; Ludvigsson, Jonas F.; Bai, Julio C. (SAGE Publications, 2015)
BACKGROUND: Celiac disease has been linked to decreased quality of life and certain mood disorders. The effect of the gluten free diet on these psychological aspects of the disease is still unclear.